Cu-Based Coatings for IT-SOFC Applications. (10th July 2019) - Tomas, Matthieu; Goebel, Claudia; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : Cu and Ce/Cu coated Sanergy HT samples were exposed at 650 °C and 850 °C for 500 h in air + 3 % water vapor and characterized. Mass gain data of all samples were measured throughout exposure. Cr-evaporation measurements were conducted and compared with uncoated Sanergy HT materials. Furthermore, SEM analysis on BIB cross-sections were performed on exposed samples. Results have shown higher mass gain for samples exposed at 850 ºC than 650 ºC as well as higher Cr evaporation. Microstructural analysis shows thinner oxide scales for samples coated with reactive elements.